Reviuw Beberapa Bioaktivitas dan Senyawa Kimia Organisme Laut untuk Kefarmasian - Laode Rijai (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
The sea as a habitat for organisms, is very characteristic and extreme compared to the terrestrial environment. This extreme environment allows the metabolic processes of living things within to become characteristic and produce a number of secondary metabolites that are characteristic for defense. Secondary metabolites are certain compounds that are only possessed by certain orgasms, and these class of compounds are very valuable for pharmaceuticals such as raw materials for medicines, nutraceuticals, cosmetics, to medical devices. A number of types of compounds with biological activity very important for pharmaceuticals originating from marine organisms are (a) Cytotoxic activities sourced from Sinularin compounds, Crassin Acetate, Cytarabine, Fludarabine, Aplysistatin, Geranylhydroquinone, Asperidol (b) Cardiovascular activities for (i) Activities for Cardiotonic namely compounds Laminin, Octopamine, Saxitoxin, Autonomium Chlorides (ii) Activities for Hypotensive namely Spongosine, Doridosine, Aaptameine, Hymenin (c) Marine Toxin, namely compounds of the group Polytoxin, such as Palytoxin; Red Tide Toxin compounds such as Tetrodotoxin, Brevetoxin in the form of Pb Tx-1 and Pb Ts-1; and Ciguatera Toxin groups, namely Ciguatoxin (d) Antimicrobial Activity such as Zonarol, Prepacifenol, Polyhalo-3-Butene-2-one; Tetrabromo-2-heptanone; 2-Cyano-4,5-dibromopyrrole, Aeroplysinin (+) and (-); Eunicin (e) Activities for Antibiotics namely Okadaic Acid, Acanthfolicin, Norhalichondrin A; and (f) Active Miscellaneous for Pharmaceuticals, namely Latrunculin A and B; Kainic Acid, Domoic Acid, Vidarabine, Aplysinopsin, Barettin, Nereistotoxin and 28-Deoxyzoanthenamine compounds.